Potential nutrient supply, nutrient utilization efficiencies, fertilizer recovery rates and maize yield in northern Nigeria - Tabi, F.O.; Diels, J.; Ogunkunle, AO; Iwuafor, E.N.O.; Vanlauwe, Bernard; Sanginga, Nteranya (Springer, 2008)
Potential N (SN) and P (SP) supplies, N and P utilization efficiencies and fertilizer recovery rates for the northern Guinea Savanna (NGS) agro-ecological zone of Nigeria were derived from data collected on farmers fields, and used as input in the QUantitative Evaluation of the Fertility of Tropical Soils (QUEFTS) model. The potential N supply ranged from 7 to 56 kg N ha?1, with a mean of 25 kg N ha?1, while SP ranged from 2 to 12 kg P ha?1 with a mean of 5 kg P ha?1. Both SN (CV = 42%) and SP (CV = 57%) were highly variable between farmers fields. Deriving potential nutrient supply from a values gives lower estimates. The empirical equation in QUEFTS that estimates SN ( SN=1.7×OC×(pH?3)) sufficiently predicted the SN of soils in the NGS (RMSE = 8.0 kg N ha?1 index of agreement (IOA) = 0.81). The SP equation ( SP=0.35×(1?0.5×(pH?6)2)×OC+0.5×OlsenP) predicted moderately potential P supply (RMSE = 6.80 kg P ha?1, IOA = 0.54). When N or P is maximally accumulated in the plant (i.e., least efficiently utilized), the utilization efficiency was 21 kg grain kg?1 N taken up and 97 kg grain kg?1 P taken up. When these nutrients were maximally diluted in the plant (i.e., most efficiently utilized), the utilization efficiency was 70 kg grain kg?1 N taken up and 600 kg grain kg?1 P taken up. The range in N recovery fraction (NRF) of N fertilizer applied was from 0.30 to 0.57, with a mean of 0.39, while the P recovery fraction (PRF) ranged from 0.10 to 0.66 with a mean of 0.24. Although SP was moderately predicted, when QUEFTS model input parameters were adjusted for the NGS, the model sufficiently (IOA = 0.83, RMSE = 607 kg DM ha?1) estimated maize grain yield in the NGS of Nigeria. The original QUEFTS model however, gave better predictions of maize grain yield as reflected by the lower RMSE (IOA = 0.84, RMSE = 549 kg DM ha?1). Consequently, QUEFTS is a simple and efficient tool for making yield predictions in the NGS of northern Nigeria.